La percepción de inseguridad relacionada con los actos delincuenciales dentro del centro urbano del cantón Echeandía, año 2021-2022. - Cisneros Álvarez, Anita Gabriela (2024)
Through the study and conceptual review of the perception of insecurity and delinquent acts, with the support of bibliographic contributions, books, articles and theses. It was established that urban neighborhood delinquent acts is a complex problem, its origin is not only due to factors such as lack of employment or money, but also depends on the environment that must be transformed to generate a sense of security that generates welfare. Currently, the perception of delinquent acts is based on each of the individual and collective experiences of the citizens living in the urban center of Canton Echeandía. This construction of delinquency, on the part of the citizens, is framed from a perception of criminal acts and the violence that this produce, in people, families, the society that conforms the urban center, a social perception of insecurity that is dominated by delinquency. Therefore, this research will be approached, using the quantitative research methodology in conjunction with the inductive method, with the descriptive level, the technique used is the survey to obtain and analyze data, to meet the object of study. Key words: Insecurity, Violence, Crime, Security.